STUDI ETNOBOTANI TUMBUHAN OBAT PADA MASYARAKAT SUKU KAILI RAI DI DUSUN SISERE, DESA LABUAN TOPOSO, KECAMATAN LABUAN, KABUPATEN DONGGALA, SULAWESI TENGAH - Agung Agung; Samsurizal M Suleman; Ramadhanil Pitopang (Biocelebes, 2018)
A research entitled “Ethnobotanical Studies of Medicinal Plant in the Kaili Rai ethnic group in Sisere Hamlet, Labuan Toposo Village, District Labuan, Donggala Regency,  Central Sulawesi” has been carried out from July until September 2016. The research objective was to obtain the information of plants diversity and its organ that utilized as traditional medicine. The research was done by two methods that is using semi structure interview technique to 38 respondents with quetioeners sheet and direct interview to village Shaman. The result showed that there were 51 plants species that used by the Kaili Rai ethnic group in the studied area The highest percentase that used in the part of plants were 65,07% of leaves and the level of community knowledge for using the plant as a traditional medicine a much as 100%. The type of the illness that can be threated are chronic, infections, non-infections and also to health care.